NUTRITION FLIPBOOK -BASED EDUCATION ON PREGNANT WOMEN'S ATTITUDES TO PREVENT STUNTING (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2025)
Background​ : Nutrition for 1,000 lives First will filled since child in content until child 2 years old . Negative attitude so inhibitor Because Mother pregnant No know nutrition . Flipbook : information media interesting audio and visual . Objectives : For know effectiveness education based flipbook  1,000 days of nutrition First life to attitude Mother pregnant in prevention stunting . Method : Type of research quantitative , design quasi- experiment t design two group pre post test design . Population: 50 pregnant women undergoing antenatal care at the Medan Denai Community Health Center from January to March 2025. The sample is an inclusion of gestational age